Impact of novel far‐infrared frying technique on quality aspects of chicken nuggets and frying medium - Udomkun, Patchimaporn; Niruntasuk, P.; Innawong, B. (Hindawi Limited, 2019)
The impact of far‐infrared and conventional heaters on heat distribution and physicochemical qualities of chicken nuggets and frying medium were investigated. For chicken nuggets, moisture content, fat content, color (L*, a*, and b*), and texture characteristics were determined, while free fatty acid (FFA), peroxide value (PV), total polar materials (TPMs), and color were used to measure the quality of frying oil. A higher heating rate and more uniform heat distribution were observed in the far‐infrared frying. Physicochemical qualities of chicken nugget were not significantly influenced by type of heater, except the fat content in the crust was significantly higher (p < 0.05) in far‐infrared fried samples. The FFA, TPM, and color values of frying oil were better in far‐infrared frying. Far‐infrared frying can be used for about 56 and 115 more cycles than conventional frying when using FFA of 0.8% and TPM of 25%, respectively as an indicator to discard the oil.